Paracrine Wingless signalling controls self-renewal of Drosophila intestinal stem cells. - Lin, G.; Xu, N.; Xi, R. (Nature, 2008)
In the Drosophila midgut, multipotent intestinal stem cells (ISCs) that are scattered along the epithelial basement membrane maintain tissue homeostasis by their ability to steadily produce daughters that differentiate into either enterocytes or enteroendocrine cells, depending on the levels of Notch activity. However, the mechanisms controlling ISC self-renewal remain elusive. Here we show that a canonical Wnt signalling pathway controls ISC self-renewal. The ligand Wingless (Wg) is specifically expressed in the circular muscles next to ISCs, separated by a thin layer of basement membrane. Reduced function of wg causes ISC quiescence and differentiation, whereas wg overexpression produces excessive ISC-like cells that express high levels of the Notch ligand, Delta. Clonal analysis shows that the main downstream components of the Wg pathway, including Frizzled, Dishevelled and Armadillo, are autonomously required for ISC self-renewal. Furthermore, epistatic analysis suggests that Notch acts downstream of the Wg pathway and a hierarchy of Wg/Notch signalling pathways controls the balance between self-renewal and differentiation of ISCs. These data suggest that the underlying circular muscle constitutes the ISC niche, which produce Wg signals that act directly on ISCs to promote ISC self-renewal. This study demonstrates markedly conserved mechanisms regulating ISCs from Drosophila to mammals. The identification of the Drosophila ISC niche and the principal self-renewal signal will facilitate further understanding of intestinal homeostasis control and tumorigenesis.